‘ABD AL-RA’ŪF AL-SINKĪLĪ : Biografi Intelektual - Puad Hasan (STIT Sirojul Falah Bogor, 2025)
This study offers a critical reappraisal of ‘Abd al-Ra’ūf al-Sinkīlī’s intellectual legacy, positing him as the pivotal figure in the reformation of 17th-century Islamic thought in the Nusantara following the doctrinal controversies initiated by Nūr al-Dīn al-Rānīrī. Moving beyond conventional biographical approaches, it argues that al-Sinkīlī’s introduction and dissemination of the Shattāriyyah Sufi order constituted the core, tangible expression of his intellectual project. Employing a descriptive-analytical methodology grounded in textual analysis of primary and limited secondary literature, this article elucidates how al-Sinkīlī’s Sufi thought reconfigured the archipelago’s intellectual landscape. A central finding highlights his characteristic Neo-Sufism, which performed a crucial reconciliatory function in the wake of al-Rānīrī’s heresy accusations against the wujūdiyyah doctrine of Ḥamzah al-Fanṣūrī. The research concludes that the Shattāriyyah order, transmitted to al-Sinkīlī via his teacher Aḥmad al-Qushāshī, served as the principal vehicle for his reformist, network-oriented Neo-Sufism, thereby cementing his role in shaping subsequent Islamic discourse in the region.